The Mental Image of The City in Turkish Painting of The Metamodernism Era - Artemenko Andrii; Yaroslava Artemenko (Sanat Tarihi Yıllığı)
In our time, special requirements are put forward for the creation of urban space. These requirements reflect the transformation processes of the city, which is a complex socio-cultural object included in the system of global connections. The design of urban space emerges as the primary reflection of the city and embodies an understanding of the city’s structure, functional use and aesthetic form. In H. Lefebvre terminology, space is created according to these concepts. The works of the artists, for whom the city has become an object of interest, take on a secondary reflection task. The reality of the modern city calls for the expression of its definition to be sought. This quest is clearly reflected in the works of Turkish artist Nuri Kuzucan. Nuri Kuzucan’s works from the two first decades of the 21st century, provide very clear data on how the ways of speaking about the city have changed. The artist's work on form in many respects repeats the search for artists of the last century. Kuzucan's creativity has three periods. Each of them corresponds to a new concept of the city at the beginning of the 21st century. In this article, it is aimed to examine the languages which are used to describe the urban culture in the beginning of the 20th century. The aim of the study, in which an interdisciplinary approach is used, is to examine the works of the contemporary Turkish artist, Nuri Kuzucan, which show the transformation process of urban culture in the paradigm of metamodernism. The methodological basis of the article is the semiotic analysis of the visual object.